Welfare state expenditures and the redistribution of well-being: Children, elders, and others in comparative perspective - Irwin Garfinkel; Lee Rainwater; Timothy M. Smeeding (Luxembourg Income Study (LIS), 2005)
This paper describes the size, nature, and redistributive effects of welfare state expenditures in ten advanced industrialized nations and relates these differences across nations to disparities in the economic well-being of country populations as a whole and three (mutually exclusive and exhaustive) sub-groups: children (and their families); elders; and childless adult households. Data from the Organization for Economic Cooperation and Development (OECD) are used to describe differences in the size and nature of welfare states. The OECD health, welfare and education benefits data are combined with micro data on household incomes from the Luxembourg Income Study (LIS) to assess their distribution and finance across the income distribution in ten countries. The results indicate a wide range of differences in levels of economic resources and support, within as well as between, nations and groups. Counting in kind benefits at government cost substantially reduces cross national differences in market and cash disposable incomes, but does not eliminate them. But the results are very sensitive to how inkind benefits, especially health insurance, are measured and valued and call into question the extra-ordinarily high US expenditures on health care.
Keywords: 330